Locating Rockfalls Using Inter‐Station Ratios of Seismic Energy at Dolomieu Crater, Piton de la Fournaise Volcano. Issue 4 (20th April 2021) - Kuehnert, J.; Mangeney, A.; Capdeville, Y.; Vilotte, J. P.; Stutzmann, E.; Chaljub, E.; Aissaoui, E.; Boissier, P.; Brunet, C.; Kowalski, P.; Lauret, F.
Abstract: Rockfalls generate seismic signals that can be used to detect and monitor rockfall activity. Event locations can be estimated on the basis of arrival times, amplitudes, or polarization of these seismic signals. However, surface topography variations can significantly influence seismic wave propagation and hence compromise results. Here, we specifically use the signature of topography on the seismic signal to better constrain the source location. Seismic impulse responses are predicted using Spectral Element based simulation of three‐dimensional wave propagation in realistic geological media. Subsequently, rockfalls are located by minimizing the misfit between simulated and observed inter‐station energy ratios. The method is tested on rockfalls at Dolomieu crater, Piton de la Fournaise volcano, Reunion Island. Both single boulder impacts and distributed granular flows are successfully located, tracking the complete rockfall trajectories by analyzing the signals in sliding time windows. Results from the highest frequency band (here 13–17 Hz) yield the best spatial resolution, making it possible to distinguish detachment positions less than 100 m apart. By taking into account surface topography, both vertical and horizontal signal components can be used. Limitations and the noise robustness of the location method are assessed using synthetic signals. Precise representation of the topography controls the location resolution, which is not significantly affected by the assumed impact direction. Tests on the network geometry reveal best resolution when the seismometers triangulate the source. We conclude that this method can improve the monitoring of rockfall activity in real time once a simulated database for the region of interest is created. Key Points: Rockfalls are located using generated seismic signals at high frequencies for highly resolved spatial and temporal tracking Rockfall location is improved using the signature of surface topography on seismic signals simulated with the three‐dimensional Spectral Element Method By accounting for topography, all signal components can be used, critical in the case of sparse station networks or noise